Plasma Parathyroid Hormone Concentration as a Predictor of Post‐Operative Hypocalcemia in Dogs Diagnosed With Primary Hyperparathyroidism and Treated With Parathyroidectomy - Victoria Travail; Claudio Motta; Charlotte Lea; Andres Salas‐Garcia; Katherine Clarke; Sergio Federico Lombardo; Amanda Paul; Dorothy Hajdu; Carla Asorey Blázquez; Mayank Seth; Michelle Walton‐Clark; Luis Miguel Garcia Roldan; et al. (Journal of Veterinary Internal Medicine)
ABSTRACT Background Hypocalcemia is a relatively common complication after parathyroidectomy for treatment of primary hyperparathyroidism. Objectives To retrospectively evaluate clinical variables in dogs with primary hyperparathyroidism to determine whether or not an association exists between pre‐surgical variables and the development of post‐surgical hypocalcemia. Animals One hundred three dogs diagnosed with primary hyperparathyroidism and treated by parathyroidectomy in seven referral hospitals between 2010 and 2021. Material and Methods Data collected from medical records included signalment, physical examination findings, concurrent illnesses, ongoing medications, and clinicopathologic test results (including serum ALP activity, iCa, plasma phosphate and PTH concentrations). Dogs were assigned into groups based on lowest iCa post‐surgery: Group1 ≥ 1.1 mmol/L, Group2 < 1.1 mmol/L. The Mann–Whitney U test assessed associations between several variables of interest and the occurrence of post‐surgery hypocalcemia. ROC analyses were performed to identify variables that had the potential to predict the development of hypocalcemia after surgery. Results The median plasma PTH concentration pre‐surgery in dogs which developed hypocalcemia after surgery was significantly higher (232 pg/mL {[IQR] 108–421}) than in dogs which did not develop hypocalcemia after surgery (81.5 pg/mL IQR 58.5–145.0; p < 0.001). Plasma PTH concentration had a fair to good ability to predict the development of post‐surgery hypocalcemia, with AUC being 0.78 [95% confidence interval 0.67–0.89]. Using a cut‐off of ≥ 75 pg/mL, pre‐surgery plasma PTH concentration had a sensitivity of 96.6% and specificity of 42.3% for the development of post‐surgery hypocalcemia. Dogs that developed hypocalcemia after surgery were older and had lower body weights. Conclusion Pre‐surgery plasma PTH concentrations might be helpful in predicting those dogs at risk of developing hypocalcemia after parathyroidectomy.